Retinoid X Receptors on survival and modulation of inflammatory response in a mouse model of Retinitis Pigmentosa - German, Olga Lorena (2016)
Retinal neurodegenerative diseases, which have no effective treatments, share as a final common step the death of photorecep- tor cells (PhR). Inflammation has a role in these pathologies as well, involving cell types having immunomodulatory capacity such as Müller glial cells (MGC). Retinoid X receptors (RXR) have the capacity of modulate and integrate multiple cell functions; and their agonists have shown beneficial clinical effects in animal models of chronic inflammatory diseases. Since little is known about RXR participation in the retina, we assessed whether this receptors might prevent PhR death and/or inflammation. Using a murine model of retinitis pigmentosa (rd mice), we analyze in vivo and in vitro the roles of RXR in retina degenera- tion. Our results using qRT-PCR show that the mRNA levels of the alpha isoform increased in the firsts postnatal days (PN) reaching the high levels at PN4 and then decreasing more in rd mice retina respect to their wt counterparts. This supports our previous data obtained by immunohistochemistry from retina slices. Noteworthy, RXR activation modulated the mRNA levels of all three RXR isoforms in mixed neuroglial cultures from rd retina. Moreover, it also delayed the onset of PhR apoptosis analyzed by TUNEL assay and decreased the protein expression of a glial marker for cell inflammatory response (GFAP) apparently without affecting its mRNA level. This last result led us to evaluate whether RXR could regulate anti-inflammatory response in the retina. Our preliminary results suggest that RXR activation increased the transcription of the anti-inflammatory cytokine interleukin (IL)-10 in rd mixed neu- roglial cultures. As a whole, the activation of RXR could promote survival of PhR either by direct action on them, or indirectly by modulating the inflammatory response of MGC